African American Women's Maternal Healthcare Experiences: A Critical Race Theory Perspective. Issue 9 (29th July 2022) - Adebayo, Comfort Tosin; Parcell, Erin Sahlstein; Mkandawire-Valhmu, Lucy; Olukotun, Oluwatoyin
ABSTRACT: Black women are experiencing pregnancy-related complications at a significantly higher rate than women of other races in the U.S., as Black women are three to four times likely to die from pregnancy-related complications compared to non-Hispanic White women. Structural barriers and different forms of marginalization continue to limit Black women's access to quality healthcare services. Through critical race theory, we examine what structural barriers exist in the U.S. healthcare system, one that limits access to quality care during their prenatal and postnatal doctor's visits. Using qualitative in-depth interviews, 31 African American women, living in Milwaukee, WI, shared their pregnancy stories. The emergent themes include, institutionalized care – racially insensitive biomedical approach, race and class – unfair treatment based on health insurance, and race as a social concept – dismissed pain concerns because you are a strong Black woman. These themes reveal the experience of racial discrimination toward African American women through healthcare [communicative] practices that are often times seen as "standard" practices, albeit marginalizing minority populations. Findings from this study offer insights for healthcare providers on communicative practices that foster a racially-safe healthcare environment for African American women.